### UNIT - III  Quadratic Expressions

1. If x2+bx+c = 0, x2+cx+b = 0 (b ≠ c) have a common root then show that b+c+1 = 0.

Sol. Let α be the common root. Then

α2 + bα + c = 0 ------------------------- (1)

α2 + cα + b = 0 -------------------------- (2)

(1) - (2) ⇒

(b-c)α + (c-b) = 0  ⇒ α = 1

(1)  ⇒ 1 + b + c = 0 or b + c + 1 = 0.

2. Find the nature of the roots of 3x2+7x+2 = 0.

Sol. Here a = 3, b = 7, c = 2.

Δ = b2-4ac = 49-4(3)(2) = 25 = 52

⇒ The roots of the given equation are rational and unequal.

3. Discuss the signs of the Quadratic expressions x2-5x+4, when x is real.

Sol: x2-5x+4 = (x-1) (x-4)

a = 1 > 0, roots are 1, 4.

x2-5x+4 > 0 if x < 1 or x > 4

x2-5x+4 < 0 if 1 < x < 4.

4. If α, β  are the roots of the equation ax2+bx+c = 0, find the values of the following expressions in terms of a, b, c.

Sol. Given α, β are roots of ax2+bx+c = 0

5. Prove that the roots of (x-a) (x-b) = h2 are always real.

Sol: Given equation is (x-a)(x-b) = h2

⇒ x2 - (a+b)x + (ab-h2) = 0

Δ = (a+b)2 - 4(1)(ab-h2)

= (a-b)2 + (2h)2 > 0

⇒  The roots are real.

6. Find the changes in the sign of the expression 15+4x-3x2 and find its extreme value.

Sol: 15+4x-3x2 = (3-x) (5+3x).

a = -3 < 0;            roots are 3, -5/3

15 + 4x -3x2 > 0        if -5/3 < x < 3

15 + 4x-3x2< 0         if x < -5/3  or x > 3.

The maximum value of 15 + 4x -3x2 is

7. Find the Quadratic equation, the sum of whose roots are 1 and the sum of the squares of the roots are 13.

Sol: Let α, β  be the roots. Then α + β = 1, α2 + β2 = 13

αβ  =  1/2 [(α + β)2 -(α2 + β2)] = [1 - 13] = -6

The required equation is x- x - 6 = 0.

8. For what values of m will the equation (m+1)x2 + 2(m+3)x + (m+8) = 0 has equal roots.

Sol: Since the given equation has equal roots discriminant Δ = 0

ie., b2 - 4ac = 0 Here a = m+1, b = 2(m+3), c = m+8

Δ  = 0   ⇒  [2(m+3)]2 - 4 (m+1) (m+8) = 0

4 (m2+9+6m) - 4 (m2+9m+8) = 0

- 12m + 4 = 0

m = 1/3.

9. Find the condition that one root of the Quadratic equation ax2+bx+c = 0 shall be n times the other, where n is a positive integer.

Sol: Let the roots be α, nα.

Sum of roots: α + nα = -b/a

⇒ α (n+1) =  -b/a

α  =

Product of roots: (α) (nα) = c/a

nα= c/a

nb2 = ac(n+1)2.

1. If the equation x2 − 15 − m(2x − 8) = 0 has equal roots, find the values of m.

Theorem 1: If a quadratic equation ax2 + bx +c = 0 has complex roots ax2 + bx + c and "a" have the same sign when x is a real number.

Proof: Given that ax2 + bx + c = 0 has complex roots, so

ax2 + bx + c and "a" both have the same sign.

Theorem 2: If a and b (a < b) are the real roots of ax2 + bx + c = 0, then

i) ax2 + bx + c and 'a' are of opposite sign when a < x < b

ii) ax2 + bx + c and 'a' are of the same sign when x < a or x > b.

Proof: If a and b are the roots of ax2 + bx + c = 0,

Theorem 3: Suppose that f(x) = ax2 + bx + c is a quadratic expression.

Solved Problems

1. Discuss the signs of the following quadratic expressions when x is real.

2. Find the maximum or minimum of the following expression as x varies over R.

3. Find the changes in the sign of the followingexpressions and find their extreme value.

4. Determine the range of the following expression.

4. Marks Questions

⇒ 3yx2 + (4y-4)x + (y-1) = 0

x ∈ R  ⇒  (4y-4)2 - 4(3y) (y-1)  0

⇒ 16y2 + 16 - 32y - 12y2 + 12y   0

⇒ 4y2 - 20y + 16   0

⇒ y2-5y + 4  0

⇒  (y-1) (y-4)  0

Roots of y2 - 5y + 4 = 0 are 1 & 4

'.' Coefficient of y2 = 1 > 0 & expression 0

y does not lie between 1 & 4.

⇒  yx2 + (-3y-1)x + (2y+p) = 0

x ∈ IR  ⇒ (-3y-1)2 - 4(y) (2y+p)  0

⇒  9y2+1 + 6y - 8y2 - 4py  0

⇒ y2 + (6-4p)y +1 0

y is real, y2 + (6-4p) y+1  0

The roots are imaginary or real and equal

⇒ (6-4p)2 - 4(1) (1)  0

⇒ 36 + 16p2 - 48p - 4  0

⇒ 16p2 - 48p + 32  0

⇒ p2 - 3p + 2  0

⇒  (p - 1) (p - 2)  0

Roots of p- 3p + 2 = 0 are 1, 2

∵ Coefficient of p2 = 1 > 0 and expression  0

1 < p < 2 and

3. If c2 ≠ ab and the roots of (c2-ab)x2 - 2(a2-bc)x + (b2-ac) = 0 are equal, then show that a3+b3+c3 = 3 abc or a = 0.

Sol. Given equation has equal roots

⇒ Discriminant Δ = b2-4ac = 0.

⇒ [-2(a2-bc)]2 - 4 (c2-ab) (b2-ac) = 0

⇒ 4(a4+b2c2-2a2bc) - 4 (c2b2-ac3-ab3+a2bc) = 0

⇒ a4+b2c2-2a2bc-c2b2+ac3+ab3-a2bc = 0

⇒ a4+ab3+ac3-3a2bc = 0

⇒ a (a3+b3+c3-3abc) = 0

⇒ a = 0 or a3+b3+c3-3abc = 0

⇒ a = 0 or a3+b3+c3 = 3 abc.

Posted Date : 24-11-2021

గమనిక : ప్రతిభ.ఈనాడు.నెట్‌లో కనిపించే వ్యాపార ప్రకటనలు వివిధ దేశాల్లోని వ్యాపారులు, సంస్థల నుంచి వస్తాయి. మరి కొన్ని ప్రకటనలు పాఠకుల అభిరుచి మేరకు కృత్రిమ మేధస్సు సాంకేతికత సాయంతో ప్రదర్శితమవుతుంటాయి. ఆ ప్రకటనల్లోని ఉత్పత్తులను లేదా సేవలను పాఠకులు స్వయంగా విచారించుకొని, జాగ్రత్తగా పరిశీలించి కొనుక్కోవాలి లేదా వినియోగించుకోవాలి. వాటి నాణ్యత లేదా లోపాలతో ఈనాడు యాజమాన్యానికి ఎలాంటి సంబంధం లేదు. ఈ విషయంలో ఉత్తర ప్రత్యుత్తరాలకు, ఈ-మెయిల్స్ కి, ఇంకా ఇతర రూపాల్లో సమాచార మార్పిడికి తావు లేదు. ఫిర్యాదులు స్వీకరించడం కుదరదు. పాఠకులు గమనించి, సహకరించాలని మనవి.

More

More

More

More